2012
DOI: 10.1038/ni.2350
|View full text |Cite
|
Sign up to set email alerts
|

Virus-cell fusion as a trigger of innate immunity dependent on the adaptor STING

Abstract: The innate immune system senses infection by detecting evolutionarily conserved molecules essential for microbial survival or abnormal location of molecules. Here we demonstrate the existence of a novel innate detection mechanism, which is induced by fusion between viral envelopes and target cells. Virus-cell fusion specifically stimulated a type I interferon (IFN) response with expression of IFN-stimulated genes (ISGs), in vivo recruitment of leukocytes, and potentiation of Toll-like re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
198
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(208 citation statements)
references
References 32 publications
9
198
0
1
Order By: Relevance
“…Zak, unpublished observations). This suggests that high and persistent Ag expression by rAd5 and chAd3 may not only result from attenuated IFN induction by these vectors but also from specific and positive regulation vated by cytosolic DNA via the action of DNA sensors, such as cyclic GMP-AMP synthase (37-39), or directly activated by bacterially generated cyclic dinucleotides (39,40) and may detect viral fusion events (41). Recent in vitro studies have shown that STING activates innate pathways after adenoviral infection (42,43) and mediates a key innate signaling pathway for sensing a variety of viruses with dsDNA or RNA genomes (44).…”
Section: Abrogation Of Type I Ifn Signaling Increases Ag Expression Amentioning
confidence: 99%
“…Zak, unpublished observations). This suggests that high and persistent Ag expression by rAd5 and chAd3 may not only result from attenuated IFN induction by these vectors but also from specific and positive regulation vated by cytosolic DNA via the action of DNA sensors, such as cyclic GMP-AMP synthase (37-39), or directly activated by bacterially generated cyclic dinucleotides (39,40) and may detect viral fusion events (41). Recent in vitro studies have shown that STING activates innate pathways after adenoviral infection (42,43) and mediates a key innate signaling pathway for sensing a variety of viruses with dsDNA or RNA genomes (44).…”
Section: Abrogation Of Type I Ifn Signaling Increases Ag Expression Amentioning
confidence: 99%
“…Recent studies indicate that STING is essential for activation of TANK-binding kinase 1 (TBK1) signaling pathways in response to herpes simplex virus-1 (HSV-1) infection. [39,40]. In the present study, we demonstrate that siRNA-mediated silencing of STING and the subsequent abrogation of downstream molecule STAT1 in human fibroblasts leads to elevated viral titers ( Figure 6).…”
Section: Mock-infected Cells (Hgps) and Ns Cells (Nhdfs) (B)mentioning
confidence: 76%
“…STING knockdown in Japanese encephalitis virus (JEV) infection model has also been found to result in increased intracellular viral load, whereas overexpression contributed to decreased viral titers [41]. Although STING is essential for IFN responses against herpes simplex virus [40], its role during VZV infection has not been previously demonstrated. STINGmediated IFN responses have been shown to be inhibited by age-enhanced endoplasmic reticulum stress during Streptococcus pneumoniae infection in an in vivo model [42].…”
Section: Mock-infected Cells (Hgps) and Ns Cells (Nhdfs) (B)mentioning
confidence: 99%
“…Повышение жесткости мембран используется еще в нескольких случаях, когда клетке не-обходимо препятствовать процессу слияния. Слияние мембран, как и патоген-ассоцииро-ванные молекулярные структуры, служит для клетки сигналом о внешнем вторжении и при-водит к активации защитных систем, посколь-ку система врожденного иммунитета содержит компонент защиты, способный различать про-цессы физиологического и нефизиологическо-го (вирусиндуцированного) слияния мембран, не реагируя при этом на первый и запуская каскад защитных реакций в ответ на второй [19]. Так, одним из интерферон-стимулируе-мых генов является семейство белков IFITM (Interferon-inducible transmembrane protein), включающее белки IFITM1, 2 и 3.…”
Section: воздействие на клеточные мишениunclassified